Stakeholder Analysis and Prioritization of Sustainable Organic Farming Management: A Case Study of Bogor, Indonesia - Adil, Adityawarman; Syarief, Rizal; Widiatmaka; Najib, Mukhamad (Sustainability, 2022)
The world’s population continues to increase, which causes food demand to increase. The increasing food demand is followed by increasing public awareness of healthy living. One way to overcome these problems is the application of organic farming. Developing organic farming must not be distinct from the role of stakeholders. The study aimed to describe and understand the stakeholders’ role in organic farming management. The research was conducted using interviews, field observations, and literature studies. The analysis was carried out quantitatively and qualitatively. Stakeholder analysis is carried out to identify, classify, map, and analyze relationships between stakeholders. The result showed all stakeholders involved in the management of organic agriculture in Bogor, West Java, are classified into four groups, namely key player (Agriculture Department and the Indonesian Organic Alliance (AOI), subject (farmers and community groups), context setter (Organic Certification Institute, Agriculture and Technology Park (ATP)-IPB University, and Organic Entrepreneurs), and the crowd (Bappeda and Universities). All stakeholders should support the government in developing policies and strategies for developing organic farming. In addition, key players, especially the Indonesian Organic Alliance, should proactively negotiate with local governments and communities regarding the sustainability of organic farming development. The policy implication of this research is to determine the contribution of stakeholders in making a strategy for the development of organic farming.